Fragmenting food markets: Some New Zealand evidence from a two-stage budget model - Mohammed Khaled; Vhari McWha; Ralph Lattimore (New Zealand Institute of Economic Research (NZIER), 2004)
Very little is known about the basic income and price responsiveness of New Zealand food markets. As far as we can determine, there has never been a complete disaggregated food demand model estimated for New Zealand. In a famous article, Court (1967) estimated a demand system for three red meats. Since then there have been a number of demand systems estimated which included food in the aggregate, but the focus in these studies was primarily on the substitution possibilities between food as a whole and other items of household expenditure. The object of this paper is to update these estimates using more recent data to see whether there are grounds for believing that the structural changes that occurred primarily during the last two decades are having effects on the size of these food demand elasticities in New Zealand. To this end, a Rotterdam food demand system is estimated for this paper using time series data from the household economic surveys, 1981 to 2001. The results indicate that over the last 20 years household consumption has increased for fruit and vegetables, poultry, food eaten away from home, and sweet products, drinks and other foods owing to time related changes in preferences and/or income growth. Fish, poultry, meat, farm products, cereals and meals away from home are all more price elastic than earlier estimates would indicate.
Keywords: C32; D12; L66; Q18; R22; 330; time series models; consumer economics; food policy; household demand; Nahrungsmittel; Produktqualität; Konsumentenverhalten; Nachfragesystem; Neuseeland